Miniature enOsCas12f1 Enables Targeted Genome Editing in Rice - Junjie Wang; Qiangbing Xuan; Biaobiao Cheng; Beibei Lv; Weihong Liang (Plants, 2025)
The type V CRISPR/Cas12f system, with its broad PAM recognition range, small size, and ease of delivery, has significantly contributed to the gene editing toolbox. In this study, enOsCas12f1 activity was detected during transient expression in rice protoplasts. The results showed that enOsCas12f1 exhibited DNA cleavage activity when it recognized TTN PAMs. Subsequently, we examined the gene editing efficiency of enOsCas12f1 in stably transformed rice plants, and the results showed that enOsCas12f1 could identify the TTT and TTC PAM sequences of the OsPDS gene, resulting in gene mutations and an albino phenotype. The editing efficiencies of TTT and TTC PAMs were 6.21% and 44.21%, respectively. Furthermore, all mutations were base deletions, ranging in size from 7 to 29 base pairs. Then, we used enOsCas12f1 to edit the promoter and 5′ UTR of the OsDREB1C gene, demonstrating that enOsCas12f1 could stably produce base deletion, mutant rice plants. Additionally, we fused the transcriptional activation domain TV with the dead enOsCas12f1 to enhance the expression of the target gene OsIPA1. Our study demonstrates that enOsCas12f1 can be utilized for rice gene modification, thereby expanding the toolbox for rice gene editing.